2018
DOI: 10.1175/jas-d-17-0218.1
|View full text |Cite
|
Sign up to set email alerts
|

Ultraclean Layers and Optically Thin Clouds in the Stratocumulus-to-Cumulus Transition. Part II: Depletion of Cloud Droplets and Cloud Condensation Nuclei through Collision–Coalescence

Abstract: In Part I, aircraft observations are used to show that ultraclean layers (UCLs) in the marine boundary layer (MBL) are a common feature of the stratocumulus-to-cumulus transition (SCT) region over the northeast Pacific. The ultraclean layers are defined as layers of either cloud or clear air in which the concentration of particles with diameter larger than 0.1 μm is below 10 cm−3. Here, idealized microphysical parcel modeling shows that in the cumulus regime, collision–coalescence can strongly deplete cloud dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…Figure 3 shows the climatology of the fraction of low clouds that are optically thin veil clouds f thin,veil from CALIOP (i.e., cloud conditional fraction). One possible explanation for such equatorward decrease in f thin,veil is that since Wood et al (2018) andO et al (2018) suggested that the detrainment mechanism from deep Cu underneath the trade inversion is the key process for the formation of optical thin veil clouds, the boundary layer over the tropics may be unfavorable for the formation of optical thin veil clouds because the inversion becomes weaker and may not preferentially concentrate the location in the vertical of detrainment levels (see Figure 2). Over the northeast pacific (NEP), f thin,veil increases westward from below 0.1 east of 135 ∘ to ∼0.3 over the SCT region.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 3 shows the climatology of the fraction of low clouds that are optically thin veil clouds f thin,veil from CALIOP (i.e., cloud conditional fraction). One possible explanation for such equatorward decrease in f thin,veil is that since Wood et al (2018) andO et al (2018) suggested that the detrainment mechanism from deep Cu underneath the trade inversion is the key process for the formation of optical thin veil clouds, the boundary layer over the tropics may be unfavorable for the formation of optical thin veil clouds because the inversion becomes weaker and may not preferentially concentrate the location in the vertical of detrainment levels (see Figure 2). Over the northeast pacific (NEP), f thin,veil increases westward from below 0.1 east of 135 ∘ to ∼0.3 over the SCT region.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Wood et al (2018) andO et al (2018) showed that a common feature associated with outflow of cumulus clusters over the SCT region is optically thin veil clouds, of which low optical thickness (i.e., < 3) is strongly contingent on its observed low-cloud droplet concentration (i.e., N d < 10 cm −3 ), and such low N d is suggested to be caused by strong precipitation scavenging process in the active cumulus. Further, O et al (2018) suggested that PBL height is a critical factor constraining coalescence scavenging process by regulating the maximum condensate amount in a cloud parcel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been a growing interest in clouds that form in the low aerosol environment found in UCLs, especially with regards to the quasi-laminar stratiform cloud layers that are likely to be detrained remnants of more active shallow cumulus O et al , 2018). These more stratiform layers, also termed veil clouds, have been characterised in the stratocumulus to cumulus transition in the north-east Pacifc and are frequently observed in POCs Terai et al , 2014).…”
Section: Ucl Clouds and The Transition Region 10mentioning
confidence: 99%